2018
DOI: 10.1111/ppl.12679
|View full text |Cite
|
Sign up to set email alerts
|

High salinity impacts germination of the halophyte Cakile maritima but primes seeds for rapid germination upon stress release

Abstract: Seed germination recovery aptitude is an adaptive trait of overriding significance for the successful establishment and dispersal of extremophile plants in their native ecosystems. Cakile maritima is an annual halophyte frequent on Mediterranean coasts, which produces transiently dormant seeds under high salinity, that germinate fast when soil salinity is lowered by rainfall. Here, we report ecophysiological and proteomic data about (1) the effect of high salt (200 mM NaCl) on the early developmental stages (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…NaCl decreased the germination percentage. This is consistent with other researches showing the saltsensitivity of C. maritima during seed germination (Debez et al 2004(Debez et al , 2018Megdiche et al 2007;Ghars et al 2009). High salinity inhibits and delays germination (Debez et al 2018) generating unfavourable osmotic conditions which prevent seed imbibition (Ghars et al 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…NaCl decreased the germination percentage. This is consistent with other researches showing the saltsensitivity of C. maritima during seed germination (Debez et al 2004(Debez et al , 2018Megdiche et al 2007;Ghars et al 2009). High salinity inhibits and delays germination (Debez et al 2018) generating unfavourable osmotic conditions which prevent seed imbibition (Ghars et al 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies documented that high saline condition only induced secondary dormancy, as non-germinated seeds remained viable, showing complete germination recovery upon salt stress removal, or appearing viable when cut opened (e.g. Del Vecchio et al 2012, 2013Murru et al 2017;Debez et al 2018). In some halophytes, salinity exposure can even promote germination recovery (Muñoz-Rodríguez et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher salt stress retards seed germination and root emergence and leads to poor crop establishment which is deleterious and prevents the plant in maintaining their proper nutritional requirements necessary for their healthy growth [3]. Reduced germination is the consequence of either direct toxic effect of salt or the general delay of the germination process caused by osmotic stress [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that SA stimulates the seed germination via bio-synthesis of gibberellic acid and acts as thermogene inducers (Shah, 2003). The reduced MGT in SA primed seeds may be attributed to the increased water uptake and promotion of the biological processes during germination provoked by SA in those seeds (Debez et al, 2018), and the reduced accumulation of Na + and Clˉ ions by SA application (Jini and Joseph, 2017). Entesari et al (2012) reported the same effect on the mung bean grown under salinity stress and primed with SA.…”
Section: Discussionmentioning
confidence: 99%